2014
DOI: 10.4236/fmar.2014.22005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Histopathologic Analysis of Placenta in Dilation and Evacuation Specimens

Abstract: Background: Anatomical and histopathologic examination of placenta in cases of abortion is crucial as to clarify the underlying causes of many adverse pregnancy outcomes. Dilation and evacuation (D&E) is the most common mode of uterine evacuation that commonly examined in pathology sections. The aim of this study is to discuss the various placental pathologies, and to demonstrate the importance of careful pathologic examination of D&E material, also to review the anatomy of placenta and to compare our findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…Most of the cases were seen at the older age group (≥30 years). In a study performed by Hassan et al, [2] molar changes were found in 5% of cases while a study conducted by Alsibiani [15] showed that partial mole was found in 0.2% of cases with mean age 33.7 ± 7.5 years that is similar to the mean age of cases in this study. However, the low incidence of molar change in the region of the study was due to sociomedical improvements.…”
Section: Types Of Histological Changes In Chorionic Villisupporting
confidence: 86%
See 4 more Smart Citations
“…Most of the cases were seen at the older age group (≥30 years). In a study performed by Hassan et al, [2] molar changes were found in 5% of cases while a study conducted by Alsibiani [15] showed that partial mole was found in 0.2% of cases with mean age 33.7 ± 7.5 years that is similar to the mean age of cases in this study. However, the low incidence of molar change in the region of the study was due to sociomedical improvements.…”
Section: Types Of Histological Changes In Chorionic Villisupporting
confidence: 86%
“…In the present study, 92 placentae examined, of which 6.5% were histologically normal placentae. A 2% of cases recorded to have calcification in this study; they were at an older age group (>40 years) compared to a study by Hassan et al [2] that revealed deposits of calcification in 12.5% of cases. The presence of these deposits is common in abortion specimens, explained by poor transport through the trophoblasts; which not utilized by the fetus due to termination of capillary flow in villi.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations